Value of a national administrative database to guide public decisions: From the système national d’information interrégimes de l’Assurance Maladie (SNIIRAM) to the système national des données de santé (SNDS) in France - Tuppin, P.; Rudant, J.; Constantinou, P.; Gastaldi-Ménager, C.; Rachas, A.; de Roquefeuil, L.; Maura, G.; Caillol, H.; Tajahmady, A.; Coste, J.; Gissot, C.; Weill, A.; et al. (Revue d'épidémiologie et de santé publique, 2017)
In 1999, French legislators asked health insurance funds to develop a système national d’information interrégimes de l’Assurance Maladie (SNIIRAM) [national health insurance information system] in order to more precisely determine and evaluate health care utilization and health care expenditure of beneficiaries. These data, based on almost 66 million inhabitants in 2015, have already been the subject of numerous international publications on various topics: prevalence and incidence of diseases, patient care pathways, health status and health care utilization of specific populations, real-life use of drugs, assessment of adverse effects of drugs or other health care procedures, monitoring of national health insurance expenditure, etc. SNIIRAM comprises individual information on the sociodemographic and medical characteristics of beneficiaries and all hospital care and office medicine reimbursements, coded according to various systems. Access to data is controlled by permissions dependent on the type of data requested or used, their temporality and the researcher's status. In general, data can be analyzed by accredited agencies over a period covering the last three years plus the current year, and specific requests can be submitted to extract data over longer periods. A 1/97th random sample of SNIIRAM, the échantillon généraliste des bénéficiaires (EGB), representative of the national population of health insurance beneficiaries, was composed in 2005 to allow 20-year follow-up with facilitated access for medical research. The EGB is an open cohort, which includes new beneficiaries and newborn infants. SNIIRAM has continued to grow and extend to become, in 2016, the cornerstone of the future système national des données de santé (SNDS) [national health data system], which will gradually integrate new information (causes of death, social and medical data and complementary health insurance). In parallel, the modalities of data access and protection systems have also evolved. This article describes the SNIIRAM data warehouse and its transformation into SNDS, the data collected, the tools developed in order to facilitate data analysis, the limitations encountered, and changing access permissions. En France, le législateur a souhaité en 1999 que les régimes d’Assurance Maladie développent un système national d’information interrégimes de l’Assurance Maladie (SNIIRAM) afin de mieux connaître et évaluer le recours aux soins et les dépenses de santé des assurés. Ces données sur près de 66 millions d’habitants en 2015 ont déjà donné lieu à de nombreuses publications internationales s’intéressant à différentes thématiques : prévalence et incidence de pathologies, parcours de soins de patients, état de santé et recours aux soins de populations spécifiques, usage des médicaments en vie réelle, mesure d’effet indésirables de médicaments ou d’autres procédures de soins, suivi des dépenses de l’Assurance Maladie, etc. Le SNIIRAM contient des informations individuelles sur des caractéristiques sociodémographiques et médicales des assurés et l’ensemble des remboursements de soins hospitaliers et de médecine de ville, codés selon différents référentiels. L’accès aux données est soumis à des autorisations qui sont fonction de la nature des données demandées ou utilisées, de leur temporalité et du statut du demandeur. De façon générale, les données peuvent être analysées par les organismes habilités sur la période couvrant les trois dernières années plus l’année en cours, et des demandes spécifiques peuvent être réalisées pour extraire des données portant sur des historiques plus longs. Un échantillon généraliste de bénéficiaires (EGB) au 1/97e, représentatif de la population protégée au niveau national, a été constitué en 2005 pour permettre un suivi sur 20 ans avec un accès facilité pour la recherche médicale. Il s’agit d’une cohorte ouverte, qui inclut les nouveaux affiliés et nouveau-nés. Le SNIIRAM a continué à évoluer mais aussi à s’étendre pour devenir, en 2016, le socle du futur système national des données de santé (SNDS) qui intègrera progressivement de nouvelles informations (causes de décès, données médicosociales et des assurances complémentaires santé). Conjointement, les modalités d’accès aux données et les systèmes de protection évoluent aussi. Cet article a pour but de décrire le SNIIRAM et l’évolution vers le SNDS, les données recueillies, les outils développés afin d’en faciliter l’analyse, les limites rencontrées, les autorisations d’accès et leurs évolutions.